The INRiM Thermo-hydraulic Mock-up for Thermal Energy Measurement Devices: Design, Construction and Metrological Characterization. (November 2015) - Marinari, C.; Saba, F.; Grisotto, F.; Orio, M.; Masoero, M.
Abstract: At the National Institute of Metrological Research (INRiM), the first European thermo-hydraulic simulator (mock-up) for testing both traditional and innovative thermal energy measurement devices and heat cost allocators has been recently built up, in the context of the EU Seventh Framework Programme FP7-SME-2012. The INRiM mock-up is an automatically reconfigurable thermo-hydraulic circuit equipped with a sufficient number of sensors aimed at measuring all the physical quantities involved in direct heat metering. It allows simulating typical central heating systems with several types of water radiators as heat exchangers and characterized by different distribution circuit topologies. The paper describes the INRiM thermo-hydraulic mock-up, highlighting its design features and metrological capabilities and discussing the first measurement results.